SEXUAL EDUCATION FOR PEOPLE WITH DISABILITIES - Bortolozzi Maia, Ana Claudia [UNESP]; Rodrigues, Marcelo Goncalves [UNESP]; Gomes, Fernando Piqueira [UNESP]; Marques, Priscila Foger [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
People with disabilities are sexual and they need clarifying and sexual education. This article describes an intervention program in sexual education for people with disabilities that have objective by: a) transmit a broad notion and emancipatory of sexuality, b) clarify and inform about education and sexual repression, c) reflect about changes in body image of the person's self-esteem with disability and implications in sexuality and d) discuss about the social belief that disability is an impediment to sexuality. The program was done in ten weekly meetings of two hours of duration and it is used of pedagogical resources such as group dynamics, videos and images. The young people participated actively, discussing and reflecting about social issues of sexuality. Concludes that the population stigmatized by disability lacks of clarifying and reflections about social construction of sexuality and of disability and that opportunities of group reflections on sexual education process for this population are fundamental in inclusive society.
Keywords: Sexual Education; Sexuality; Disability